2015
DOI: 10.1073/pnas.1506109112
|View full text |Cite
|
Sign up to set email alerts
|

Histamine in the basolateral amygdala promotes inhibitory avoidance learning independently of hippocampus

Abstract: Recent discoveries demonstrated that recruitment of alternative brain circuits permits compensation of memory impairments following damage to brain regions specialized in integrating and/or storing specific memories, including both dorsal hippocampus and basolateral amygdala (BLA). Here, we first report that the integrity of the brain histaminergic system is necessary for long-term, but not for short-term memory of step-down inhibitory avoidance (IA). Second, we found that phosphorylation of cyclic adenosine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
6
34
0
Order By: Relevance
“…As a-FMHis effect on histamine synthesis persists for about 48 h (22), it is conceivable that rats receiving a-FMHis prior to IA training lacked integrity of the histaminergic system during the consolidation process, whereas those treated 24 h after training, during the retrieval. These findings confirm that histamine depletion impairs the consolidation of IA memory (17) and suggest that it also worsens IA-LTM expression by influences on memory retrieval mechanisms. To further test these hypotheses, we investigated whether intracerebral administration of histamine reversed the amnesic effect of histamine depletion caused by a-FMHis.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As a-FMHis effect on histamine synthesis persists for about 48 h (22), it is conceivable that rats receiving a-FMHis prior to IA training lacked integrity of the histaminergic system during the consolidation process, whereas those treated 24 h after training, during the retrieval. These findings confirm that histamine depletion impairs the consolidation of IA memory (17) and suggest that it also worsens IA-LTM expression by influences on memory retrieval mechanisms. To further test these hypotheses, we investigated whether intracerebral administration of histamine reversed the amnesic effect of histamine depletion caused by a-FMHis.…”
Section: Resultssupporting
confidence: 78%
“…We recently showed that intra-LV infusion of a-FMHis (5 μg/μL) quickly and fully suppressed the release of brain histamine measured by microdialysis, which was restored to control levels after about 48 h (17). Thus, to investigate the role of endogenous histamine in retrieval, we examined the performance of rats infused into the LV with a-FMHis 24 h after the IA training session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it can be concluded from the present data that the CA1 region of the dorsal hippocampus and the BLA are key participants in the regulation of SRM in rats, and that norepinephrine acting on β-receptors, dopamine acting on D1/D5 receptors, and histamine acting on H2 receptors in these two brain regions play a pivotal role in social recognition measured in a standard social discrimination paradigm. The roles of the catecholamines (14,18,38), and to an extent that of histamine (16,36), appear peculiarly interesting because they probably affect this (3) and other forms of memory (14) by actions in the hippocampus and BLA, mediated by the enhanced synthesis of the nuclear CREB (3,16,38), which is related to protein synthesis, here shown to be necessary for SRM, as previously posited by Kogan et al (3).…”
Section: Discussionmentioning
confidence: 71%
“…In the case of SRM, Kogan et al (3) showed that, in mice, SRM is dependent upon protein synthesis and cyclic adenosine monophosphate responsive-element-binding protein (CREB) function in the hippocampus. Given the fact that the hippocampus and the basolateral amygdala (BLA) work in close association in the making and the regulation of many types of memory (13)(14)(15)(16)(17), we decided to study the participation of both structures in SRM. Historically, the next step to ascertain a putative brain mechanism in a behavior is to examine the eventual role of known neurotransmitters in those structures within the mechanism (13,15).…”
mentioning
confidence: 99%